The determinants of employees job performance at Perbadanan Majukan Iktisad Negeri Terengganu / Hannah Hamizah Roslan - Roslan, Hannah Hamizah (2014)
Perbadanan Memajukan Iktisad Negeri Terengganu is one of the companies that accelerating the development plans of urban and rural and also improve and strengthen the economic base by creating pure Bumiputera Commercial and Industrial Community. The researcher studied the determinants of employees's job performance towards Perbadanan Memajukan Iktisad Negeri Terengganu, Kuala Terengganu.